Pengaruh Internet Marketing Terhadap Pembentukan Word Of Mouth dan Efektivitas Iklan Dalam Meningkatkan Brand Awareness - Zettira, Zara; Aditi, Bunga; Pentana, Sopi (Cattleya Darmaya Fortuna, 2024)
This study aims to determine the effect of internet marketing on word of mouth, the effect of internet marketing on advertising effectiveness, the effect of word of mouth on brand awareness, the effect of advertising effectiveness on brand awareness, the influence of internet marketing on brand awareness, the influence of internet marketing on brand awareness through word of mouth. of mouth and the influence of internet marketing on brand awareness through advertising effectiveness. The total population in this study amounted to 110 people and all of them were sampled using a saturated sample. The analysis technique used is path analysis. The results show that internet marketing has a significant effect on word of mouth, internet marketing has no effect on advertising effectiveness, internet marketing has no effect on brand awareness, word of mouth has no effect on brand awareness, advertising effectiveness has no effect on brand awareness, there is no significant influence on the internet. marketing on brand awareness through word of mouth and there is no significant influence of internet marketing on brand awareness through the effectiveness of advertising on social media Instagram Energen Indonesia